Repeated Gastrointestinal Disease Reporting and Subsequent Multidomain Health Deterioration: Longitudinal Analyses in CHARLS and ELSA - Ding Peng; Huihong Zhai (Geriatrics & Gerontology International, 2026)
ABSTRACT Aim To examine whether repeated gastrointestinal disease reporting was associated with subsequent multidomain health deterioration and whether the direction of association was consistent across two national aging cohorts. Methods CHARLS was the primary longitudinal cohort. Participants with at least two gastrointestinal exposure assessments across waves 1–3 were classified as never, intermittent/low, or persistent/high reporting. The primary composite comprised cognitive, ADL, IADL, or depressive‐symptom deterioration. Logistic and robust Poisson models were fitted. ELSA provided a cross‐cohort consistency analysis using a pre‐Wave‐1 gastrointestinal disease/medication proxy. Results CHARLS included 12 144 participants/5607 events; fully adjusted models included 9555/4523. Adjusted relative risks were 1.10 (95% CI 1.03–1.18) for intermittent/low and 1.06 (1.01–1.11) for persistent/high reporting. In ELSA, the fully adjusted three‐level education model included 3286/1752 and yielded an odds ratio of 1.24 (0.97–1.59); the longitudinal‐weighted estimate was 1.21 (0.90–1.63). Gastrointestinal exposure produced negligible incremental discrimination in either cohort. Conclusions Repeated gastrointestinal reporting was associated with a small increase in subsequent deterioration in CHARLS, while ELSA estimates were directionally similar but less precise. Gastrointestinal history may prompt broader geriatric assessment but is not a stand‐alone predictor or evidence of causality.